Effects of Telerehabilitation on Upper Limb Function Activities of Patients with Chronic Stroke - Isariyapan, Olan; Nanta, Chiratchaya; Poommuang, Supitcha; Srivichai, Apichaya; Chondaen , Natchaya; Roongpiboonsopit, Duangnapa; Wiwatmanitsakul, Jirasin; Srisoparb, Waroonnapa (Journal of Thai Stroke Society, 2024)
This study examined the impact of telerehabilitation on upper limb functional activities (ULFA) in individuals with chronic stroke. Ten participants underwent the telerehabilitation program consisting of a 70-minute session, five times a week for four weeks. The program included a combination of strength training and task-oriented training (TOT). ULFA, grip strength, upper limb motor impairments, muscle tone and quality of life were assessed by the Streamlined Wolf Motor Function Test-Chronic (SWMFT-C), Grip strength dynamometer, Fugl-Meyer assessment of Upper extremities (FMA-UE), Modified Ashworth Scale and Stroke Impact Scale (SIS), respectively. The findings revealed statistically significant improvements (p<0.05) in SWMFT-C, grip strength, FMA-UE, and SIS scores across the strength, hand function, and percentage of recovery domains following the training program. Video-based telerehabilitation, incorporating both strength training and TOT, notably enhances ULFA and contributes to an improved quality of life for chronic stroke patients.